Testing the Effectiveness of Law Enforcement and Analyzing Obstacles in Document Forgery Investigations: A Critical Study at the Gorontalo Police Resort - Rintjap, Arianty Junita; Wantu, Fence M.; Achir, Nuvazria (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the effectiveness of law enforcement and identify obstacles in investigating document forgery cases at the Gorontalo Police Resort. The research method used is juridical-empirical with a qualitative approach, combining literature study on regulations and empirical data through interviews and case documentation. The results show that the effectiveness of law enforcement is still not optimal, reflected in the low case resolution rate compared to the number of incoming reports. The main obstacles include the limited number and competence of investigators, lack of forensic laboratory facilities, and high administrative burdens. Additionally, external factors such as low public legal awareness, witness reluctance, and poor coordination among law enforcement agencies slow down the investigation process. Improvement efforts focus on enhancing human resource capacity, strengthening coordination, legal education for the public, and utilizing technology in the investigation process. This study recommends the need for cross-sector synergy and strengthening monitoring systems to improve the effectiveness of law enforcement against document forgery crimes at the local level.